Chapter 13 Outlook - Brunner, Esther (Taylor & Francis, 2021)
In many countries, early mathematics education rests on normative postulates. Moreover, it tends to be considerably less standardized and, at the same time, more pronouncedly situation-specific than school education. Given these differences, the professional skills of early childhood teachers have come into the focus of research and the question arises to what extent general models of professional skills can be directly transferred to the context of early childhood teachers. Based on the “opportunity-usage model of teaching”, this contribution attempts to determine more precisely what influences teaching is basically subject to. Subsequently, I will ask how early mathematics education differs from general education and what the rationales and the level-specific postulates of early mathematics education consist in. The outline of the specifics of early mathematics education and the field of work leads to a characterization of the professional group that enacts this teaching and to the question as to what professional skills early childhood teachers need. Against this background, the final section suggests an extension of the model of the transformation of professional skills, and briefly outlines open questions and future lines of research.